Kształcenie badawcze w czasach globalizacji z perspektywy europejskiej - Niemczyk , Ewelina K.; Pogorzelska, Marzanna (Studia Edukacyjne, 2019)
This qualitative research study takes a closer look at developing competent researchers and thus building research capacity within Europe. The rapidly changing research environment driven by globalisation, internationalization, technological advancements, and the use of innovative methodologies impacts how research is designed, conducted, and reported on. We argue that the current complex research environment calls for globally competent researchers able to engage in research projects and research communities across disciplines and across geographic borders. However, there is scarce empirical evidence about research knowledge and competencies which global researchers need to conduct quality research. Relevant literature is also almost silent on what kind of educational opportunities within higher education institutions allow graduate students to acquire these competencies. To address the existing gap in the literature, this article brings perspectives of twenty-three novice and experienced scholars from ten European countries. The findings showcase a spectrum of competencies required by globally competent researchers as well as opportunities and challenges associated with the acquisition of these competencies. According to the respondents, efforts need to be maximized to build research capacity via emerging talents. This implies paying close attention to the research learning spaces, practices, and polices where future globally competent researchers can be nurtured and shaped. Considering the small sample size of participants, the findings are not meant to be conclusive but rather informative in nature for those involved in research.